Appraisal of Feeding Practices for Pet Dogs in Districts of Central Punjab - Singh, Opinder; Singh, Udeybir; Mavi, Gurjot; Grewal, R. S.; Sethi, A. P. S. (International Journal of Livestock Research, 2020)
Under the present study, total 222 dog owners, eighty (46 from urban and 34 from rural), seventy-five (35from urban and 40 from rural) and sixty-seven (34 from urban and 33 from rural) dog owners of the Amritsar, Tarn Taran and Jalandhar districts, respectively were surveyed. Data regarding the feeding practices were recorded and feed samples of dog feed were collected. Dog owners are mainly giving the homemade food. Consumption of milk and curd is significantly (P≤0.05) higher in both the urban and rural areas of Amritsar whereas milk product consumption is significantly lesser in urban area of Amritsar. Sweet consumption is highest recorded in urban area of Tarn Taran as compared to both areas of other districts. Non –vegetarian diet is highest in both urban and rural areas of Amritsar and Tarn Taran as compared to Jalandhar. Significant difference has been found in the milk, milk product, curd, chapatti, dal, rice and meat in urban and rural dogs in Amritsar district as compared to other two districts. The physiochemical properties of dog diet revealed that coliform and free fatty acid is found to be highest in Amritsar and lowest in Jalandhar. pH and standard plate count found to be non-significant among all the districts. Based on the data available, it is clearly indicated that there is wide variation in feeding practices adopted in various districts as well as rural and urban area of a district.